The Concept of Marriage Guardian in the Perspective of Islamic Law - Faizah, Nur (Cv. Kalimasada Group, 2023)
Marriage Guardian (wali nikah) is one of the pillars of marriage in Islam that must be fulfilled for marriage to be considered valid. In the perspective of Islamic law, the marriage guardian has a very important role because without the presence or permission of the guardian, the marriage can be considered invalid. Marriage guardian is generally a man who has the closest blood relationship to the prospective bride, such as a father, brother, or other relative. The main task of the guardian is to give permission or approval for the marriage of the woman he is guardian of, with the aim of protecting the rights and honor of the prospective bride and keeping the marriage in accordance with Islamic law. In the fiqh literature, there are different views among scholars regarding the type of guardian and the conditions that must be met by the guardian, such as whether guardianship must be given by the nasab guardian (blood relative) or wali hakim (legal authority) if the nasab guardian is absent. This study aims to examine the position of marriage guardians in Islamic law, by reviewing the shar'i arguments and views of various madhhabs regarding the validity of marriage and the responsibilities of guardians.